Effects of soil temperature and moisture on methane uptakes and nitrous oxide emissions across three different ecosystem types - Luo, G.J.; Kiese, Ralf; Wolf, B.; Butterbach-Bahl, Klaus (Copernicus GmbH, 2013)
In this paper, we investigate similarities of effects of soil environmental drivers on year-round daily soil fluxes of nitrous oxide and methane for three distinct semi-natural or natural ecosystems: temperate spruce forest, Germany; tropical rain forest, Queensland, Australia; and ungrazed semi-arid steppe, Inner Mongolia, China. Annual cumulative fluxes of nitrous oxide and methane varied markedly among ecosystems, with nitrous oxide fluxes being highest for the tropical forest site (tropical forest: 0.96 kgNha−1 yr−1; temperate forest: 0.67 kgNha−1 yr−1; steppe: 0.22 kgNha−1 yr−1), while rates of soil methane uptake were approximately equal for the temperate forest (−3.45 kgC ha−1 yr−1) and the steppe (−3.39 kgC ha−1 yr−1), but lower for the tropical forest site (−2.38 kgC ha−1 yr−1). In order to allow for cross-site comparison of effects of changes in soil moisture and soil temperature on fluxes of methane and nitrous oxide, we used a normalization approach. Data analysis with normalized data revealed that, across sites, optimum rates of methane uptake are found at environmental conditions representing approximately average site environmental conditions. This might have rather important implications for understanding effects of climate change on soil methane uptake potential, since any shift in environmental conditions is likely to result in a reduction of soil methane uptake ability. For nitrous oxide, our analysis revealed expected patterns: highest nitrous oxide emissions under moist and warm conditions and large nitrous oxide fluxes if soils are exposed to freeze–thawing effects at sufficiently high soil moisture contents. However, the explanatory power of relationships of soil moisture or soil temperature to nitrous oxide fluxes remained rather poor (R2 ≤0.36). When combined effects of changes in soil moisture and soil temperature were considered, the explanatory power of our empirical relationships with regard to temporal variations in nitrous oxide fluxes were at maximum about 50 %. This indicates that other controlling factors such as N and C availability or microbial community dynamics might exert a significant control on the temporal dynamic of nitrous oxide fluxes. Though underlying microbial processes such as nitrification and denitrification are sensitive to changes in the environmental regulating factors, important regulating factors like moisture and temperature seem to have both synergistic and antagonistic effects on the status of other regulating factors. Thus we cannot expect a simple relationship between them and the pattern in the rate of emissions, associated with denitrification or nitrification in the soils. In conclusion, we hypothesize that our approach of data generalization may prove beneficial for the development of environmental response models, which can be used across sites, and which are needed to help achieve a better understanding of climate change feedbacks on biospheric sinks or sources of nitrous oxide and methane.